CONTINUING EDUCATION IN PROMOTING HEALTH FROM AN INTERINSTITUTIONAL ACTION - Quesada Monge, Ana Cristina (2014)
There is a consensus about the definition of promoting health but not about its approach since many authors have identified differences with regard to its implementation and how to address it.  As a consequence, there have appeared difficulties for it to operate not only focusing on the biologistmedical-welfare paradigms because this makes actions to be guided only to the prevention of disease. In this paper, we present the general and regional theoretical references that produced two projects of teaching extension and the methodologies and results of these projects.